The Opinions of Academic Members of Ahvaz University of Medical Sciences about the Effective Factors on their Evaluation Score Variations - Mehri Ghafourian Boroujerdnia; Abdol Hossein Shakurnia; Hossein Elhampour (Kerman University of Medical Sciences, 2006)
Background: Considering the importance of educational processes in our universities evaluation of academic members in order to improve their teaching quality is highly necessary In Education Development Center of Ahvaz University of Medical Sciences evaluation of academic members by students is performed annually through questionnaires and the results are reflected to the teachers Objective: To determine the opinions of teachers about the effective factors on variations of their evaluation score during the academic year of 20032004 in comparison to the previous year Methods: In this descriptive study a researchermade questionnaire was prepared and distributed among 130 non clinical academic members of whom 72% filled and returned the questionnaires Data were analyzed by computing frequency percentage and Chisquare test Results: About half of the teachers (523%) gained a higher evaluation score in comparison to the previous year and they believed that the most important factors causing this increase have been respectively more proficiency in educational program content (46%) considering students program level (26%) knowing the results of previous evaluation (23%) participating in medical education workshops (75%) improvement of educational facilities (71%) and alteration in social behavior (68%) Among all teachers 374% gained a lower score comparing to the previous year and according to them frequent holidays during the academic semester (49%) type of course and its nature (37%) and students dishonesty in evaluating teachers (34%) had been the most important factors affecting decrease in their evaluation score while inappropriate class time (91%) had not been effective in this regard Conclusion: In order to improve the quality of educational programs considering academic members suggestions and trying to resolve educational problems are highly recommended